Island in the stars - Lloyd, Natalie (The Problim children, 2021)
Mystery and mayhem abound in the final book in New York Times bestselling author Natalie Lloyd's middle grade series, as the Problim siblings board a pirate ship to rescue their missing Mama and baby brother from the villainous Cheesebreath, now available in paperback.